Racism and the fight against racism: notes on the Spanish "comprehensive strategy" against racism - Cachón, Lorenzo (Razón y fe, 2018)
No one is free from hatred. No one in Spain, in the midst of our adverse circumstances, can claim that racism does not affect them. Racism, for very different reasons, has become one of our challenges, a contemporary challenge. If we do not want it to invade and determine us, we should make the contents of the so-called "Strategy against racism, discrimination, xenophobia and other related to intolerance". This will be the only way to dislodge discrimination and racism, more present than it seems among us.